Characterisation of the nuclear proteome of a dehydration‐sensitive cultivar of chickpea and comparative proteomic analysis with a tolerant cultivar. Issue 12 (21st June 2013) - Subba, Pratigya; Kumar, Rajiv; Gayali, Saurabh; Shekhar, Shubhendu; Parveen, Shaista; Pandey, Aarti; Datta, Asis; Chakraborty, Subhra; Chakraborty, Niranjan
Abstract : Water deficit or dehydration hampers plant growth and development, and shrinks harvest size of major crop species worldwide. Therefore, a better understanding of dehydration response is the key to decipher the regulatory mechanism of better adaptation. In recent years, nuclear proteomics has become an attractive area of research, particularly to study the role of nucleus in stress response. In this study, a proteome of dehydration‐sensitive chickpea cultivar (ICCV‐2) was generated from nuclei‐enriched fractions. The LC‐MS/MS analysis led to the identification of 75 differentially expressed proteins presumably associated with different metabolic and regulatory pathways. Nuclear localisation of three candidate proteins was validated by transient expression assay. The ICCV‐2 proteome was then compared with that of JG‐62, a tolerant cultivar. The differential proteomics and in silico analysis revealed cultivar‐specific differential expression of many proteins involved in various cellular functions. The differential tolerance could be attributed to altered expression of many structural proteins and the proteins involved in stress adaptation, notably the ROS catabolising enzymes. Further, a comprehensive comparison on the abiotic stress‐responsive nuclear proteome was performed using the datasets published thus far. These findings might expedite the functional determination of the dehydration‐responsive proteins and their prioritisation as potential molecular targets for better adaptation.